Sophilos, Son of Aristotle, of Phyle - Tracy, Stephen V. (Hyperboreus, 2017)
Soon after the disastrous defeat of the Athenian army at Chaironeia in 338 BC Sophilos, son of Aristotle, from Phyle emerged as a prominent leader in Athens. He cooperated with Lykourgos and others in rebuilding Athenian power and prestige. In particular, he served as General over the Countryside for the years 334/3 and 333/2. In that position he played an important role in guiding the military training of the ephebes. The renewal of the ephebic corps constituted one of the key elements in Lykourgos’ program. The present article discusses all of the evidence for Sophilos’ activities and adds a new piece.